Effect of 8 Weeks of Overfeeding on Ectopic Fat Deposition and Insulin Sensitivity: Testing the “Adipose Tissue Expandability” Hypothesis - Johannsen, Darcy L. (American Diabetes Association, 2014)
OBJECTIVE: The presence of large subcutaneous adipocytes in obesity has been proposed to be linked with insulin resistance and type 2 diabetes through the “adipose tissue expandability” hypothesis, which holds that large adipocytes have a limited capacity for expansion, forcing lipids to be stored in nonadipose ectopic depots (skeletal muscle, liver), where they interfere with insulin signaling. This hypothesis has, however, been largely formulated by cross-sectional findings and to date has not been prospectively demonstrated in the development of insulin resistance in humans. RESEARCH DESIGN AND METHODS: Twenty-nine men (26.8 ± 5.4 years old; BMI 25.5 ± 2.3 kg/m(2)) were fed 40% more than their baseline requirement for 8 weeks. Before and after overfeeding, insulin sensitivity was determined using a two-step hyperinsulinemic-euglycemic clamp. Intrahepatic lipid (IHL) and intramyocellular lipid (IMCL) were measured by (1)H-MRS and abdominal fat by MRI. Subcutaneous abdominal adipose and skeletal muscle tissues were collected to measure adipocyte size and markers of tissue inflammation. RESULTS: Subjects gained 7.6 ± 2.1 kg (55% fat) and insulin sensitivity decreased 18% (P < 0.001) after overfeeding. IHL increased 46% from 1.5% to 2.2% (P = 0.002); however, IMCL did not change. There was no association between adipocyte size and ectopic lipid accumulation. Despite similar weight gain, subjects with smaller fat cells at baseline had a greater decrease in insulin sensitivity, which was linked with upregulated skeletal muscle tissue inflammation. CONCLUSIONS: In experimental substantial weight gain, the presence of larger adipocytes did not promote ectopic lipid accumulation. In contrast, smaller fat cells were associated with a worsened metabolic response to overfeeding.